Collisionality dependence of edge rotation and in–out impurity asymmetries in ASDEX Upgrade H-mode plasmas. (23rd October 2015) - Viezzer, E.; Fable, E.; Pütterich, T.; Bergmann, A.; Cavedon, M.; Dux, R.; McDermott, R.M.; Angioni, C.; Churchill, R.M.; Dunne, M.G.; Laggner, F.M.; Lipschultz, B.; et al.
Abstract: The poloidal and toroidal impurity flows in the edge transport barrier of H-mode plasmas have been studied over a wide range of pedestal top ion collisionalities. A comparison of the edge poloidal rotation measurements to neoclassical predictions shows good agreement in all cases. The measured edge impurity toroidal rotation is observed to change sign from co-current to counter-current with decreasing collisionality. The switch occurs at the same collisionality at which neoclassical theory predicts the main ion poloidal rotation to change from the electron to the ion diamagnetic direction. The behaviour of these two species, when used to calculate the main ion toroidal rotation via the radial force balance equation, leads to fairly constant co-current main ion toroidal rotation. Hence, at low collisionality, due to a reduced frictional coupling, the main ion-impurity differential rotation can be quite large. The behaviour of impurity ion flows on a flux surface has also been investigated in detail and it was found that the measurements are consistent with the continuity equation only if the poloidally asymmetric impurity density distribution is taken into account. The asymmetry is found to be the result of the interplay of all forces in the parallel momentum balance, with the friction force providing the dominant drive. Close to the separatrix the poloidal centrifugal force, which is usually neglected, also gives an additional contribution to the impurity density asymmetry. Within the experimental uncertainties the ion temperature and the electrostatic potential are simultaneous flux functions, despite the presence of a poloidally asymmetric impurity density profile.